2020
DOI: 10.1515/psr-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Understanding (coupled) large amplitude motions: the interplay of microwave spectroscopy, spectral modeling, and quantum chemistry

Abstract: A large variety of molecules contain large amplitude motions (LAMs), inter alia internal rotation and inversion tunneling, resulting in tunneling splittings in their rotational spectrum. We will present the modern strategy to study LAMs using a combination of molecular jet Fourier transform microwave spectroscopy, spectral modeling, and quantum chemical calculations to characterize such systems by the analysis of their rotational spectra. This interplay is particularly successful in decoding complex spectra re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 212 publications
(291 reference statements)
0
26
0
Order By: Relevance
“…Microwave spectroscopy is classically connected with the topic of structural chemistry, because the primary parameters deduced from a microwave spectrum, the rotational constants, directly reflect the mass distribution of the atoms in the molecule [1]. However, along the history of almost one century since the first microwave spectrum of ammonia was measured in 1934 [2], large amplitude motions (LAMs) have been involved, either in the form of inversion motion [3], ring puckering [4], or internal rotation [5]. If the molecule features a methyl group undergoing internal rotation, a torsional fine structure consisting of A-E doublets can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave spectroscopy is classically connected with the topic of structural chemistry, because the primary parameters deduced from a microwave spectrum, the rotational constants, directly reflect the mass distribution of the atoms in the molecule [1]. However, along the history of almost one century since the first microwave spectrum of ammonia was measured in 1934 [2], large amplitude motions (LAMs) have been involved, either in the form of inversion motion [3], ring puckering [4], or internal rotation [5]. If the molecule features a methyl group undergoing internal rotation, a torsional fine structure consisting of A-E doublets can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prominent LAM manifestation is the tunneling splitting of the ground vibrational state, whenever a motion between equivalent minima is involved. Such splittings can be observed, for instance, using microwave (MW) or millimeter wave (MMW) rotational spectroscopy [6][7][8][9][10][11][12][13][14][15]. A knowledge of the LAM and of its characteristics can be helpful for the interpretation of the experimental data [11,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to challenges in both spectral assignment and fit, only a limited number of two-top molecules have been investigated, as reviewed by Nguyen and Kleiner. 2 Unlike inequivalent two-top cases where the point group of the frame symmetry can be C 1 or C s , in the cases of two equivalent methyl groups, due to the higher molecular symmetry requirement, e.g., C 2 , C 2h , or C 2v , the number of studies reported in the literature are even smaller. Some examples of equivalent two-top molecules are dimethylgermane, 5 dimethylamine, 6 dimethylketene, 7 isobutylene, 8 propane, 9 2,6-lutidine, 10,11 difluorodimethylsilane, 12 2-bromopropane, 13 dimethyl sulfate, 14 acetone, 15,16 dimethyl ether, 17 diethyl ketone, 18 dimethyl sulfide, 19 2,5-dimethylthiophene, 20 2,5-dimethylfuran, 21 and 2,6dimethylfluorobenzene.…”
Section: Introductionmentioning
confidence: 99%